Opistognathus pardus, a new species of jawfish (Teleostei: Opistognathidae) from the Western Indian Ocean - Smith-Vaniz, William F.; Bineesh, K. K.; Akhilesh, K. V. (Zootaxa, 2012)
A new species of jawfish, Opistognathus pardus, is described based on a single specimen, 98.8 mm SL, recently collectedfrom the Western Indian Ocean off Quilon (Kerala), India. The combination of a rigid maxilla without flexible lamina pos-teriorly, a unique color pattern in which most of the head is covered with small, irregular-shaped, dark spots, dorsal-finrays XI, 11, and the outermost segmented pelvic-fin ray tightly bound to adjacent ray, with the interradial membrane notincised distally distinguishes the new species from other congeners. This is the fourth species of Opistognathus known from the coast of India or Sri Lanka. A range extension for O. macrolepis is also reported.